Does nitrogen doping enhance the electrocatalysis of the oxygen reduction reaction by multiwalled carbon nanotubes? - Lu, YL; Li, X; Kumar, AKS; Compton, RG (American Chemical Society, 2022)
Single-entity electrochemistry measurements were used to compare the electrocatalysis of the oxygen reduction reaction (ORR) by means of multiwalled carbon nanotubes (MWCNTs) or amino-functionalized multiwalled carbon nanotubes (MWCNTs-NH2). All of the evidence showed that an electroactive surface oxygen functionality played the most important role in the catalysis process, not the nitrogen content.